Anisotropic properties of directed energy deposition (DED)-processed Ti–6Al–4V. (October 2016) - Wolff, Sarah; Lee, Taekyung; Faierson, Eric; Ehmann, Kornel; Cao, Jian
Abstract: Directed energy deposited (DED) Ti–6Al–4V components and prototypes are quickly growing in prevalence in aerospace and biomedical industries for their increased strength and fast processing time. However, one of the remaining challenges in DED processes, particularly laser engineered net shaping (LENS), is the characterization of the inherent anisotropy in material properties. Anisotropy in microstructure, porosity and mechanical behavior arises due to unique material thermal histories during processing. Understanding anisotropy in additive manufacturing can lead to refined process parameters, characterization methods, material and thermal modeling as well as improved mechanical properties. This paper investigates the anisotropic mechanical properties, specifically ultimate tensile strength, of LENS-processed Ti–6Al–4V and how these properties depend on geometry and direction of build processing. Mechanical properties were found to be most desirable when the tensile orientation is orthogonal to the build direction and parallel to the scan direction as well as closer to the center of a fully dense component. This study investigates microstructure through X-ray diffraction, fractography and porosity shape and connectivity analysis. Models that predict mechanical behavior based on processing details are in development. There is potential to achieve desirable mechanical properties through melt pool and thermal controls for high-strength and energy efficient materials by predicting mechanical properties from process parameters.